(untitled) (Educational Dimension, 2020)
The reform of the continuing teachers’ training system in Ukraine is meant to provide teachers with the opportunities for professional development and lifelong learning according to the requirements set by the State education policy, employers and key stakeholders. This implies creation of flexible competitive educational environment using mobile advanced training programs and modernization of content, forms, methods techniques of teaching. The authors present a set of andragogic and psychological assessment instruments to use for continuing teachers’ training, including feedback questionnaires, complex questionnaires, blitz polls, tests, selection of monitoring methods on teachers’ professional and lifelong development.